(untitled) (Revista Apotheke, 2024)
There is a winning aesthetic movement in the twentieth century. It imposed itself above all the others. This movement is the expressionism. Its razing predominance, as universal aesthetic proposal, has been asserted with all its variants in much of the contemporary art system and, concurrently, in many teaching practices of visual arts schools. Given that in our teaching practice we detect obvious difficulties expressed by visual arts students regarding pictorial composition, we propose a contemporary re-reading, study and reinterpretation of the geometric processes used in various ways by the ancient masters.